Assembleia Legislativa de Mato Grosso e o retorno presencial à escola na pandemia: as relações de força entre política, educação e saúde (2020-2022) - Martins, Elen Carolina (Universidade do Vale do Rio dos Sinos, 2025)
This dissertation aimed to investigate the proposals that the Legislative Assembly of Mato Grosso (ALMT) adopted in light of the medical and health recommendations of competent national and international bodies and institutions, to legislate on the return to in-person classes in the context of the Coronavirus 2019 (Covid-19) pandemic, from 2020 to 2022. The general objective was to analyze these proposals, considering the possible relationships between them and the political and socio-educational context of this Federative Unit. The questions presented in the investigation were: how can the proposals of the Legislative Assembly of Mato Grosso be analyzed, in light of the medical and health recommendations, when legislating on the return to in-person classes, from 2020 to 2022? What would be the relationships between these proposals and the composition of forces within the ALMT, as well as with the socio-political and educational context in which legislators act? The chosen methodological approach was documentary analysis, based on the perspectives of André Cellard (2012). The empirical basis for answering the research questions was constituted by documents produced by national and international health agencies, as well as by bills on the subject, which were processed by the ALMT. In response to the research problem, the thesis defended is that the ALMT, with its actions and omissions, produced effects in the context of practice. Such effects were defined by the alignment of the parliamentary majority with the government project defended by the state Executive. The latter, aligned with the federal Executive, was guided by the defense of a denialist, antivaccine stance and defender of the immediate interests of the economic and business sectors, to the detriment of the interests of the majority of the population, directly influencing the conditions for the return to in-person classes in the pandemic context.
Keywords: Políticas Públicas em Educação; Poder Legislativo; Pandemia de Covid 19; Assembleia Legislativa do Mato Grosso; Retorno à presencialidade nas escolas; Public Policies in Education; Legislative branch; Covid 19 Pandemic; Legislative Assembly of Mato Grosso; Return of in-person classes in schools; ACCNPQ::Ciências Humanas::Educação